2013
DOI: 10.1002/jcu.22060
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocolonic sonography: A complete colorectal evaluation technique with preliminary results

Abstract: HUS is a low-cost and noninvasive procedure for colorectal study. This technique has the potential to be used for the detection of colorectal cancer and polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
0
1
1
Order By: Relevance
“…With the data obtained, HS cannot be considered a suitable technique for studying the rectum, since, as other authors have also found [6,19,20], our results were poor. The lower portion of the rectum was not visible [7], since the colon was distended from the rectal ampulla.…”
Section: Discussioncontrasting
confidence: 66%
“…With the data obtained, HS cannot be considered a suitable technique for studying the rectum, since, as other authors have also found [6,19,20], our results were poor. The lower portion of the rectum was not visible [7], since the colon was distended from the rectal ampulla.…”
Section: Discussioncontrasting
confidence: 66%
“…Bu yönüyle özellikle pediatrik hasta grubunda tercih edilebilir. 8 BT kolon duvar kalınlığın araştırılmasında, kolorektal poliplerin tespit edilmesinde kullanılabilir. 9 Ayrıca BT kolonografi kolorektal lezyonların araştırılmasında etkin bir inceleme yöntemidir.…”
Section: Discussionunclassified